A cobalt-copper double-atomic nitrogen oxygen coordination carbon material, a preparation method and application thereof

CN122974352APending Publication Date: 2026-10-27HAINAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611402512.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]催化活性与选择性不足:传统过渡金属/碳氮共掺杂材料(M-N-C)作为电芬顿阴极催化剂时,两电子氧还原(2e-ORR)过程的选择性较低,导致H2O2的原位产量和激发效率无法满足微塑料长链高分子降解的需求

Benefits of technology

1.配位环境的精准调控与高催化活性:本发明采用ZIF-8作为前驱体,创新性地引入三聚氰酸与钴、铜金属发生dsp轨道杂化作用进行配位,精细调控了钴铜双原子的配位环境。有效克服了传统氮配位双原子催化剂选择性差、活性低的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application provides a cobalt-copper double-atom nitrogen-oxygen coordination carbon material and a preparation method and application thereof; the material preparation method provided by the application is as follows: (1) cobalt-copper double-metal salt and cyanuric acid are sequentially added into a methanol solution of ZIF-8 and stirred, and then a precursor is prepared through solid-liquid separation, cleaning and drying; (2) the precursor is carbonized at high temperature in an inert atmosphere to obtain the atom-level dispersed cobalt-copper-based nitrogen-oxygen doped carbon material. The material prepared by the application realizes efficient generation and activation of H2O2 in seawater through coordination regulation of double-atom active centers, and degrades microplastics through multiple free radical paths.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrocatalyst technology, and in particular to a cobalt-copper dual single-atom nitrogen-oxygen coordinated carbon material, its preparation method, and its application. Background Technology

[0002] Microplastics, as a novel persistent organic pollutant, pose a serious threat to global aquatic ecosystems and human health due to their stable chemical structure, reluctance to degrade, and tendency to accumulate in organisms. Among existing water treatment technologies, electro-Fenton technology, as an advanced oxidation process, reduces dissolved oxygen (O2) to hydrogen peroxide (H2O2) through a cathode reaction, triggering the in-situ generation of highly oxidizing hydroxyl radicals (·OH). This process can efficiently mineralize microplastics into CO2 and H2O, offering significant advantages such as mild reaction conditions, no secondary pollution, and ease of operation. However, most current electro-Fenton degradation research is based on freshwater systems (accounting for only 3% of global water resources). In contrast, seawater, which accounts for 96% of global water resources, while possessing advantages such as high conductivity and near-neutral pH (natural electrolytes), faces the following significant challenges in implementing electro-Fenton technology in seawater systems: Chloride ion poisoning and side effects: Seawater contains a high concentration (approximately 0.5 M) of chloride ions (Cl). - It readily adsorbs onto the metal active sites of the catalyst, occupying active sites and causing catalyst "poisoning"; at the same time, side reactions may occur at the anode or cathode to produce residual chlorine, reducing the overall energy utilization efficiency.

[0003] Insufficient catalytic activity and selectivity: When traditional transition metal / carbon-nitrogen co-doped materials (MNC) are used as electro-Fenton cathode catalysts, the two-electron oxygen reduction (2e... - The low selectivity of the ORR process means that the in-situ yield and activation efficiency of H2O2 cannot meet the requirements for the degradation of long-chain polymers in microplastics.

[0004] In recent years, single-atom catalysts (SACs) have attracted much attention due to their theoretical 100% atom utilization. To further improve catalytic performance, the development of diatom catalysts (DACs) with adjacent bimetallic sites has become a new trend. Diatom catalysts can overcome the limitations of single-atom site ratios through synergistic metal-metal interactions. However, the application of diatom catalysts in current technologies still faces the following bottlenecks: The underlying mechanism of regulating the coordination environment is unclear: how to precisely fine-tune the coordination environment of the metal ion center (such as by introducing heteroatoms) to change the electron density distribution around it, and thus regulate the catalyst activity and resistance to chlorine poisoning, remains unclear.

[0005] Lack of customized designs for microplastic degradation in seawater: Currently, there is a lack of a solution that can efficiently address both 2e and 3e issues. - ORR produces H2O2, and can efficiently activate H2O2 in situ to generate highly active free radicals, and can also repel Cl. - Adsorbed anti-poisoning diatomic catalyst.

[0006] Therefore, developing a novel, precisely coordinated co-doped cobalt-copper biatomic catalyst (CoCu-N(O) / C) and clarifying its efficient and interference-resistant degradation mechanism for microplastics in complex seawater media is of great economic and ecological significance for promoting the application of electro-Fenton technology to practical marine environmental governance. Summary of the Invention

[0007] In view of this, the present invention proposes a cobalt-copper dual single-atom nitrogen-oxygen coordinated carbon material, its preparation method and application, to solve the above problems.

[0008] The technical solution of this invention is achieved as follows: a cobalt-copper dual single-atom nitrogen-oxygen coordinated carbon material and its preparation method. (1) The zinc source solution was mixed with the imidazole ligand solution, and after solid-liquid separation, washing and drying, the zeolite imidazole ester framework material (ZIF-8) was obtained. (2) The cobalt source, copper source, cyanuric acid and the zeolite imidazole ester framework material are mixed in a solvent, and the mixture is subjected to solid-liquid separation, washing and drying to obtain the precursor; (3) The precursor is subjected to high-temperature heat treatment in an inert atmosphere to obtain the cobalt-copper double single-atom nitrogen-oxygen coordinated carbon material.

[0009] Further, in step (1), the volume ratio of the imidazole ligand solution to the zinc source solution is 1:(0.8~1.2); the imidazole ligand solution is a methanol solution of 2-methylimidazolium with a concentration of 30-50 g / L, and the zinc source solution is a zinc salt solution with a concentration of 30-50 g / L.

[0010] Furthermore, the zinc salt solution is a methanol solution of zinc nitrate hexahydrate.

[0011] Further, in step (2), the cobalt source is a cobalt salt, and the copper source is a copper salt; the cobalt salt is any one or more of cobalt nitrate, chloride, sulfate, acetylacetonate, and acetate; the copper salt is any one or more of copper nitrate, chloride, sulfate, acetylacetonate, and acetate; and the solvent is methanol.

[0012] Further, the molar ratio of the cobalt salt to the copper salt is (3:1) to (1:3), the molar ratio of ZIF-8 to the total molar amount of the cobalt salt and copper salt is 300mg:(0.01~0.1)mmol, and the mass ratio of ZIF-8 to cyanuric acid is 1:(0.005~0.1).

[0013] Furthermore, in steps (1) and (2), the centrifugal washing process involves centrifuging and washing with methanol several times until the pH value is 6-8.

[0014] Further, in step (3), the precursor is ground into powder and then subjected to high-temperature heat treatment. The inert atmosphere is nitrogen. The high-temperature heat treatment is carried out under the protection of nitrogen atmosphere, with the temperature rising to 900~1100℃ at a rate of 1~10℃ / min and held for 1~5h.

[0015] An atomically dispersed cobalt-copper-based nitrogen-oxygen-doped carbon material was prepared using the method described above.

[0016] Furthermore, the sum of the contents of cobalt and copper in the cobalt-copper dual single-atom nitrogen-oxygen coordinated carbon material is 0.03~1wt%.

[0017] Application of a cobalt-copper dual-monatomic nitrogen-oxygen coordinated carbon material in the electro-Fenton degradation of microplastics in seawater.

[0018] Compared with the prior art, the beneficial effects of the present invention are: 1. Precise control of coordination environment and high catalytic activity: This invention uses ZIF-8 as a precursor and innovatively introduces cyanuric acid to coordinate with cobalt and copper metals through dsp orbital hybridization, thus precisely controlling the coordination environment of the cobalt-copper diatomic catalyst. This effectively overcomes the problems of poor selectivity and low activity of traditional nitrogen-coordinated diatomic catalysts.

[0019] 2. Excellent adaptability to seawater environment: This atomically dispersed cobalt-copper-based nitrogen-oxygen-doped carbon material exhibits excellent stability and electro-Fenton catalytic performance in complex seawater matrices, and can efficiently generate reactive oxygen species, providing an efficient and green solution for the in-situ degradation of marine microplastics. Attached Figure Description

[0020] Figure 1 X-ray diffraction patterns of ZIF-8 and CoCu(O)-ZIF-8 prepared in Example 1.

[0021] Figure 2 The X-ray diffraction pattern of CoCu-N(O) / C prepared in Example 1 is shown.

[0022] Figure 3 Scanning electron microscope image of CoCu(O)-ZIF-8 prepared in Example 1.

[0023] Figure 4 Scanning electron microscope image of CoCu-N(O) / C prepared in Example 1.

[0024] Figure 5 Aberration-corrected scanning transmission electron microscope image and energy dispersive spectroscopy of CoCu-N(O) / C prepared in Example 1.

[0025] Figure 6 The average number of electrons transferred during the oxygen reduction process of CoCu-N(O) / C prepared in Example 1.

[0026] Figure 7 The yield of H2O2 in the oxygen reduction process of CoCu-N(O) / C prepared in Example 1.

[0027] Figure 8 The degradation rate of different microplastics by electro-Fenton degradation in 0.5M NaCl solution of CoCu-N(O) / C prepared in Example 1 was measured.

[0028] Figure 9 The degradation rate of polypropylene (PP) microplastics prepared by CoCu-N(O) / C in Example 1 after 6 cycles of electro-Fenton degradation in 0.5M NaCl solution.

[0029] Figure 10 This is a particle size distribution diagram of PP before degradation.

[0030] Figure 11 The particle size distribution of PP microplastics after electro-Fenton degradation in 0.5M NaCl solution using CoCu-N(O) / C prepared in Example 1 is shown.

[0031] Figure 12 The degradation rate of PP by electro-Fenton degradation in 0.5M NaCl solution was measured using catalysts prepared for comparative examples 1, 2, and 3. Detailed Implementation

[0032] To better understand the technical content of this invention, specific embodiments are provided below to further illustrate the invention.

[0033] Unless otherwise specified, the experimental methods used in the embodiments of this invention are all conventional methods.

[0034] Unless otherwise specified, all materials and reagents used in the embodiments of this invention are commercially available.

[0035] Example 1 The preparation method of the atomically dispersed cobalt-copper-based nitrogen-oxygen-doped carbon material in this embodiment is carried out according to the following steps: (1) Weigh 4.928g of 2-methylimidazole and dissolve it in 120mL of methanol, which is named solution A. Weigh 4.464g of zinc nitrate hexahydrate and dissolve it in 120mL of methanol, which is named solution B. Mix solution A and solution B and stir vigorously. The resulting product is washed several times by centrifugation with methanol until the supernatant is neutral. Then it is dried to obtain ZIF-8 sample. (2) Weigh 0.30g of ZIF-8 sample, 8.7mg of cobalt nitrate trihydrate, 7.2mg of copper nitrate trihydrate, and 5mg of cyanuric acid, dissolve them in 90mL of methanol and stir. The resulting product is washed several times by centrifugation with methanol until the supernatant is neutral, and the precursor sample (CoCu(O)-ZIF-8) is obtained. (3) Weigh 0.2g of precursor, grind it into powder, spread it evenly in a corundum crucible, and place it in the middle of the tube furnace cavity for calcination. Under the protection of nitrogen atmosphere, the temperature is raised to 950℃ at a heating rate of 5℃ / min and held for 2h to obtain the calcined sample (CoCu-N(O) / C). The ZIF-8 sample, precursor sample (CoCu(O)-ZIF-8), and calcined sample (CoCu-N(O) / C) prepared above were characterized and their performance was tested. 1. Crystal structure and morphology testing (1) The crystal structures of ZIF-8, its precursor, and CoCu-N(O) / C were characterized using the MiniFlex600 crystallizer from Rigaku Corporation, Japan. The results are as follows: Figure 1 and Figure 2 As shown. From Figure 1 The obvious characteristic peaks of ZIF-8 are clearly visible, fully demonstrating the successful preparation of ZIF-8. Furthermore, the addition of the metal salt and cyanuric acid did not disrupt the ZIF-8 framework. Figure 2 As shown, none of the pyrolysis samples exhibited characteristic peaks of metal oxides or metal particles, preliminarily indicating that the metal particles were dispersed as single atoms.

[0036] (2) The overall morphology of CoCu(O)-ZIF-8 and CoCu-N(O) / C was analyzed using scanning electron microscopy. For example... Figure 3 and Figure 4 As shown, the precursor has a regular morphology, which is a rhombic dodecahedron, and the morphology is maintained after high-temperature pyrolysis.

[0037] (3) The atomic states of CoCu-N(O) / C were analyzed using aberration-corrected scanning transmission electron microscopy. For example... Figure 5 As shown, the bright spots represent metal atoms. It can be seen that the metal atoms are all isolated, indicating that the metal sites in the catalyst are dispersed as single atoms and are evenly distributed, which is beneficial to improving the catalytic performance.

[0038] 2. Electrochemical performance testing (1) The oxygen reduction electrocatalytic performance of CoCu-N(O) / C was tested using an electrochemical workstation (Donghua DH7000) and a rotating ring / disk electrode (Ivium, Netherlands).

[0039] The electrocatalytic activity and stability of CoCu-N(O) / C in the oxygen reduction reaction were tested using linear sweep voltammetry and cyclic voltammetry. The glassy carbon electrode surface was polished with alumina powder of different particle sizes and then rinsed clean. 2 mg of CoCu-N(O) / C was dissolved in a mixed solvent of 720 μL isopropanol, 240 μL deionized water, and 40 μL Nafion. The solution was ultrasonicated for 1 hour to ensure complete and uniform dispersion. Then, 2 μL of the slurry was pipetted onto the polished glassy carbon electrode surface. After drying, the electrochemical loading of CoCu-N(O) / C on the glassy carbon electrode was 0.032 mg·cm³. -2 An electrochemical testing system using a standard three-electrode system was employed, with a rotating ring / disk electrode as the working electrode, a platinum wire as the counter electrode, and a silver / silver chloride electrode as the reference electrode (electrolyte: 0.5M NaCl). A glassy carbon electrode with a catalyst-containing surface (4 mm in diameter) was used as the working electrode.

[0040] During the test intervals, oxygen must be continuously introduced to ensure that the electrolyte is saturated with oxygen. The scan rate of the disk electrode in the linear voltammetry test was set to 0.02 V / s, the voltage test window was 0.05~1.05 V (vs. RHE), and the rotation speeds were set to 2500 rpm, 2025 rpm, 1600 rpm, 1225 rpm, 900 rpm, 625 rpm, and 400 rpm. The step potential of the ring electrode was set to 1.2 V (vs. RHE). Data was collected under the 1600 rpm condition, and the H2O2 selectivity and electron transfer number were calculated using the following formula: H2O2%=200×( I R / N) / ( I D + I R / N) n=4× I D / ( I D + I R / N) in, I D and I R These are disk current and ring current, respectively.

[0041] The electron transfer number and H2O2 selectivity obtained under neutral simulated seawater conditions (0.5M NaCl) are shown in the figure. Figure 6 , 7 .like Figure 6 , 7 As shown, within the potential range of 0.1-0.4V, the average number of electrons transferred by the catalyst is 3.1, which is very close to 3, indicating that the oxygen reduction reaction mainly proceeds via the 3-electron transfer pathway.

[0042] (2) The electrocatalytic degradation performance of CoCu-N(O) / C microplastics was tested using an electrochemical workstation (Donghua DH7000).

[0043] The electrocatalytic degradation performance of CoCu-N(O) / C in neutral simulated seawater was tested using a chronoamperometry method with constant potential. 2 mg of CoCu-N(O) / C was dissolved in a mixed solvent of 960 μL isopropanol and 40 μL Nafion, and the solution was sonicated for 1 hour to ensure complete and uniform dispersion. Then, 250 μL of the slurry was transferred to a spray gun and evenly sprayed onto a 1×1 cm² surface. 2 On carbon paper, the loading was 0.5 mg / cm³. 2 A standard three-electrode electrochemical testing system was used, with carbon paper as the working electrode, a platinum sheet as the counter electrode, a silver / silver chloride electrode as the reference electrode, 80 mL of 0.5 M NaCl as the electrolyte, and 8 mg of microplastic particles as the substrate. Using the aforementioned catalyst-coated carbon paper as the working electrode, a constant potential of -0.7 V (vs RHE) was applied during the test, with continuous stirring at 300 rpm and oxygen introduced at a flow rate of 400 mL / min. The electrocatalytic degradation of microplastics was completed in 6 hours.

[0044] The degradation rates of different microplastics (polyvinyl chloride (PVC), polyethylene terephthalate (PET), polyamide (PA), and polylactic acid (PLA)) under the above conditions are shown in the figure. Figure 8 .like Figure 8 As shown, this catalyst exhibits excellent electro-Fenton degradation performance for a variety of microplastics.

[0045] Under the above conditions, the degradation rate of PP microplastics after 6 cycles is shown in the figure. Figure 9 .like Figure 9 As shown, after 6 cycles, the degradation rate still remained above 70% of that in the first cycle.

[0046] The particle size distribution of PP microplastics before and after degradation under the above conditions is shown in the figure. Figure 10 , 11 .like Figure 10 , 11 As shown, the particle size of PP microplastics is significantly reduced after degradation.

[0047] Example 2 This embodiment provides a cobalt-copper dual single-atom nitrogen-oxygen coordinated carbon material. The only difference between its preparation method and that of Example 1 is that the calcination conditions in step (3) are different, while the other steps are the same as those in Example 1.

[0048] The specific steps are as follows: (1) Same as step (1) in Example 1, to obtain ZIF-8 sample.

[0049] (2) Same as step (2) in Example 1, to obtain the precursor sample (CoCu(O)-ZIF-8).

[0050] (3) Weigh 0.2g of precursor, grind it into powder, spread it evenly in a corundum crucible, and place it in the middle of the tube furnace cavity for calcination. Under the protection of nitrogen atmosphere, the temperature is raised to 1000℃ at a heating rate of 5℃ / min and held for 3h to obtain the calcined sample (CoCu-N(O) / C).

[0051] Comparative Example 1 This comparative example provides a comparative material whose preparation method differs from Example 1 only in that cyanuric acid is not added in step B; the remaining steps are the same as in Example 1. Specifically, the steps are as follows: (1) Same as step (1) in Example 1, to obtain ZIF-8 sample.

[0052] (2) Weigh 0.30g of ZIF-8 sample, 8.7mg of cobalt nitrate trihydrate and 7.2mg of copper nitrate trihydrate, dissolve them in 90mL of methanol and stir. The resulting product is washed several times by centrifugation with methanol until the supernatant is neutral, and the precursor sample (CoCu-ZIF-8) is obtained.

[0053] (3) Same as step (3) in Example 1, to obtain the calcined sample (CoCu-N / C).

[0054] Comparative Example 2 This comparative example provides a comparative material whose preparation method differs from that of Example 1 only in that cobalt salt is not added in step (2), while the remaining steps are the same as in Example 1. Specifically, the steps are as follows: (1) Same as step (1) in Example 1, to obtain ZIF-8 sample.

[0055] (2) Weigh 0.30g of ZIF-8 sample, 14.4mg of copper nitrate trihydrate and 5mg of cyanuric acid, dissolve them in 90mL of methanol and stir. The resulting product is washed several times by centrifugation with methanol until the supernatant is neutral, and the precursor sample (Cu(O)-ZIF-8) is obtained.

[0056] (3) Same as step (3) in Example 1, to obtain the calcined sample (Cu-N(O) / C).

[0057] Comparative Example 3 This comparative example provides a comparative material whose preparation method differs from that of Example 1 only in that urea is used instead of cyanuric acid in step (2), while the remaining steps are the same as in Example 1. Specifically, the steps are as follows: (1) Same as step (1) in Example 1, to obtain ZIF-8 sample.

[0058] (2) Weigh 0.30g of ZIF-8 sample, 8.7mg of cobalt nitrate trihydrate, 7.2mg of copper nitrate trihydrate and 7mg of urea, dissolve them in 90mL of methanol and stir. The resulting product is washed several times by centrifugation with methanol until the supernatant is neutral, and the precursor sample (CoCu(O)-ZIF-8-U) is obtained.

[0059] (3) Same as step (3) in Example 1, to obtain the calcined sample (CoCu-N(O) / Cu).

[0060] Following the electrocatalytic degradation test method for microplastics described in Example 1, samples prepared in Comparative Examples 1, 2, and 3 were tested for polypropylene (PP) microplastic degradation under the same conditions. The results showed that, as Figure 12 As shown, the degradation rates of PP microplastics in the samples prepared in Comparative Examples 1, 2 and 3 were significantly lower than those in Example 1, indicating that the nitrogen-oxygen dual coordination environment introduced by the nitrogen- and oxygen-containing ligand (cyanuric acid) and the synergistic effect of cobalt and copper diatoms play a key role in improving the performance of seawater electro-Fenton degradation of microplastics.

[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a cobalt-copper dual single-atom nitrogen-oxygen coordinated carbon material, characterized in that, Includes the following steps: (1) The zinc source solution was mixed with the imidazole ligand solution, and after solid-liquid separation, washing and drying, zeolite imidazole ester skeleton material was obtained; (2) The cobalt source, copper source, cyanuric acid and the zeolite imidazole ester framework material are mixed in a solvent, and the mixture is subjected to solid-liquid separation, washing and drying to obtain the precursor; (3) The precursor is subjected to high-temperature heat treatment in an inert atmosphere to obtain the cobalt-copper double single-atom nitrogen-oxygen coordinated carbon material.

2. The preparation method of the cobalt-copper dual single-atom nitrogen-oxygen coordinated carbon material as described in claim 1, characterized in that, In step (1), the volume ratio of the imidazole ligand solution to the zinc source solution is 1:(0.8~1.2); the imidazole ligand solution is a methanol solution of 2-methylimidazolium with a concentration of 30-50 g / L, and the zinc source solution is a zinc salt solution with a concentration of 30-50 g / L.

3. The preparation method of the cobalt-copper dual single-atom nitrogen-oxygen coordinated carbon material as described in claim 2, characterized in that, The zinc salt solution is a methanol solution of zinc nitrate hexahydrate.

4. The preparation method of the cobalt-copper dual single-atom nitrogen-oxygen coordinated carbon material as described in claim 1, characterized in that, In step (2), the cobalt source is a cobalt salt, and the copper source is a copper salt; the cobalt salt is any one or more of cobalt nitrate, chloride, sulfate, acetylacetonate, and acetate; the copper salt is any one or more of copper nitrate, chloride, sulfate, acetylacetonate, and acetate; and the solvent is methanol.

5. The preparation method of the cobalt-copper dual single-atom nitrogen-oxygen coordinated carbon material as described in claim 4, characterized in that, The molar ratio of the cobalt salt to the copper salt is (3:1) to (1:3), the molar ratio of the zeolite imidazole ester framework material to the total amount of the cobalt salt and copper salt is 300 mg: (0.01~0.1) mmol, and the mass ratio of the zeolite imidazole ester framework material to cyanuric acid is 1: (0.005~0.1).

6. The method for preparing the cobalt-copper dual single-atom nitrogen-oxygen coordinated carbon material as described in claim 1, characterized in that, In steps (1) and (2), the centrifugal washing process involves washing with methanol several times until the pH value is 6-8.

7. The method for preparing the cobalt-copper dual single-atom nitrogen-oxygen coordinated carbon material as described in claim 1, characterized in that, In step (3), the precursor is ground into powder and then subjected to high-temperature heat treatment. The inert atmosphere is nitrogen. The high-temperature heat treatment is carried out under the protection of nitrogen atmosphere, with the temperature rising to 900~1100℃ at a heating rate of 1~10℃ / min and held for 1~5h.

8. A cobalt-copper dual single-atom nitrogen-oxygen coordinated carbon material prepared by the preparation method according to any one of claims 1 to 7.

9. The cobalt-copper dual single-atom nitrogen-oxygen coordinated carbon material according to claim 8, characterized in that, The total content of cobalt and copper in the cobalt-copper dual single-atom nitrogen-oxygen coordinated carbon material is 0.03~1wt% by mass.

10. The application of the cobalt-copper dual-monatomic nitrogen-oxygen coordinated carbon material as described in claim 1 in the electro-Fenton degradation of microplastics in seawater.